Substance Abuse Rehabilitation Services and Programs in the UAE: Analytical Study - Aljasmi, Alyaa; AlHorani, Mohamed (Al-Adab Journal, 2025)
The United Arab Emirates offers a pioneering humanitarian approach that emphasizes human service and care, whether on a local or worldwide basis. Therefore, the UAE has implemented a continual expansion and enhancement strategy for institutions and service providers across multiple fields. In substance abuse treatment field, UAE is committed to provide specialized substance abuse centres for patients and their families. These services have a workforce of highly skilled professionals. They provide an extensive range of services, such as detoxification, rehabilitation and treatment services, individual and family counselling, and continuous aftercare services. All these efforts should follow the international guidelines and standards of excellence to ensure that individuals receive care based on scientific evidence during the rehabilitation journey. This paper examines a review about addiction treatment and rehabilitation centres in the UAE, including Al Amal Hospital, the National Rehabilitation Centre, the Erada Centre for Treatment and Rehab, and the Ownak Aftercare Centre. In addition, this report will highlight UAE efforts from a legal and strategic perspective, highlighting the recent changes in substance abuse law and Abu Dhabi Strategy to combat drug abuse 2022-2024. Moreover, this study attempts to demonstrate evidence-based guidelines for effective substance abuse rehabilitation and research-based behavioural approaches that are published by the National Institute on Drug Abuse. The method used in preparing this scientific paper is the documentary method, which depend on mainly on gathering secondary resources.